Thermal design optimization of evaporator micropillar wicks - Somasundaram, Sivanand (2020)
Heat pipes and vapor chambers act as efficient heat spreaders since they rely on phase change of the coolant. The evaporator design is critical and typically high performance is characterized by the high heat dissipation capability with low thermal resistance. In the past, there have been numerous experimental and modeling studies focused on the design of evaporator wicks of different geometries, but systematic studies to simultaneously optimize both the heat flux and thermal resistance have been limited. In this work, we developed a comprehensive model that considers both aspects to provide design guidelines for evaporator micropillar wicks. We show that capillary limited heat dissipation is best captured with a recently developed numerical model as compared to previous analytical models. We also developed a numerical model to obtain the effective wick thermal conductivity, which is a function of pillar diameter, pitch, and height. Smaller diameters with smaller pitches of the pillars had more thin film area and had larger effective wick thermal conductivities. Our parametric investigations show that trade-offs between lowest thermal resistance and maximum heat carrying load exists, and the actual wick geometry will be dictated by application specific requirements. Finally, we highlight the importance of accurately obtaining the accommodation coefficients to predict the effective wick thermal conductivity. The present work would enable in optimal design of micropillar wicks (with low thermal resistance and high dry-out heat flux) and the same methodology can be extended to other types of wick structures as well.